(untitled) (Raparin Journal of Humanities (RJH), 2024)
A recent study investigated the level of psychological resilience of women with breast cancer in the center of Erbil Governorate. It holds the following objectives: (i) to examine the prevalence level of psychological resilience among women with breast cancer. (ii) to examine the difference in the level of psychological resilience according to variables (Degree of cancer and social status). The population of the research comprises women with breast cancer in the center of Erbil governorate, the researcher selected simple random sampling, which included (225) women with breast cancer. To measure the research variable, the researcher built the scale of psychological resilience, which includes (30) items. The researcher accomplished the scale’s face validity and discriminatory power and maintained all the scale items. The researcher measured the reliability through the half-segmentation method, the value was (0.77), and based on the Spearman-Brown equation the value reached (0.87). The research shows that women suffer from breast cancer because of a lack of psychological resilience. The study further demonstrates statistically significant differences in psychological resilience according to the degree of cancer. There is a statistically significant difference in psychological resilience according to the social status variable in favor of married women. Based on the current findings the researcher mentioned several necessary recommendations and suggestions.